2015
DOI: 10.1038/ncomms7251
|View full text |Cite
|
Sign up to set email alerts
|

One-shot K-region-selective annulative π-extension for nanographene synthesis and functionalization

Abstract: The optoelectronic nature of two-dimensional sheets of sp2-hydridized carbons (for example, graphenes and nanographenes) can be dramatically altered and tuned by altering the degree of π-extension, shape, width and edge topology. Among various approaches to synthesize nanographenes with atom-by-atom precision, one-shot annulative π-extension (APEX) reactions of polycyclic aromatic hydrocarbons hold significant potential not only to achieve a ‘growth from template’ synthesis of nanographenes, but also to fine-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
108
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(111 citation statements)
references
References 52 publications
(69 reference statements)
1
108
1
Order By: Relevance
“…127 The direct palladium-catalysed C-H arylation with o-chloranil as the oxidant was shown to occur exclusively at the K-regions of PAHs, which allowed their selective two-step p-extension, for instance, from phenanthrene to dibenzo[g,p]chrysene. 206 Additionally, Scott et al also reported iridiumcatalysed five-fold borylation of corannulene (39) to afford 1,3,5,7,9-pentakis(BPin)corannulene (BPin = (pinacolato)boron), which provided facile access to a defined molecular fragment of [5,5] 206 Additionally, Scott et al also reported iridiumcatalysed five-fold borylation of corannulene (39) to afford 1,3,5,7,9-pentakis(BPin)corannulene (BPin = (pinacolato)boron), which provided facile access to a defined molecular fragment of [5,5] …”
Section: Direct Edge Functionalization Of Graphene Moleculesmentioning
confidence: 99%
“…127 The direct palladium-catalysed C-H arylation with o-chloranil as the oxidant was shown to occur exclusively at the K-regions of PAHs, which allowed their selective two-step p-extension, for instance, from phenanthrene to dibenzo[g,p]chrysene. 206 Additionally, Scott et al also reported iridiumcatalysed five-fold borylation of corannulene (39) to afford 1,3,5,7,9-pentakis(BPin)corannulene (BPin = (pinacolato)boron), which provided facile access to a defined molecular fragment of [5,5] 206 Additionally, Scott et al also reported iridiumcatalysed five-fold borylation of corannulene (39) to afford 1,3,5,7,9-pentakis(BPin)corannulene (BPin = (pinacolato)boron), which provided facile access to a defined molecular fragment of [5,5] …”
Section: Direct Edge Functionalization Of Graphene Moleculesmentioning
confidence: 99%
“…A variety of synthetic methodologies for constructing various π-extended PAHs have been developed towards achieving high efficiency and novelty56789101112131415. Among them, since the seminal advance has been made by Müllen and Spiess et al .…”
mentioning
confidence: 99%
“…Seven isomers including two pairs of enantiomers of 1 could be generated by the combination of the chirality of each [4]helicene moiety (P or M) as shown in Figure 3. The twisted form 1a observed by X-ray crystallography was the most stable conformation among the five ground states 1a-e.…”
Section: Cluster Syn Lettmentioning
confidence: 99%
“…The end-toend twisted angle of the tetracene moiety of 1 is 80.5°, which is higher than those of previously reported unsubstituted benzannulated acenes. 9 The highly twisted structure of 1 was realized by the combination of four [4]helicene substructures. The packing mode of 1 in the crystal is shown in Figure 2 one-dimensional π-π stacking of the nonplanar π-systems was found.…”
Section: Cluster Syn Lettmentioning
confidence: 99%
See 1 more Smart Citation